Optimization of the operation of the anthropomorphic manipulator in a three-dimensional working space. Issue 11 (2nd November 2019) - Skrobek, Dorian; Cekus, Dawid
ABSTRACT: This article presents the use of the particle swarm method to optimize the working cycle of an anthropomorphic manipulator. The working space contained stationary obstacles which made the working cycle difficult. Three objective functions were adopted in the study, concerning trajectory minimization, reduction of electricity consumption and multi-criteria optimization (minimization of both trajectory length and electricity consumption). The effects of selected parameters on the particle swarm optimization (PSO) algorithm and the results of the examinations were analysed.